2016
DOI: 10.1101/sqb.2016.81.031377
|View full text |Cite
|
Sign up to set email alerts
|

RON Signaling Is a Key Mediator of Tumor Progression in Many Human Cancers

Abstract: With an increasing body of literature covering RON receptor tyrosine kinase function in different types of human cancers, it is becoming clear that RON has prominent roles in both cancer cells and in the tumor-associated microenvironment. RON not only activates several oncogenic signaling pathways in cancer cells, leading to more aggressive behavior, but also promotes an immunosuppressive, alternatively activated phenotype in macrophages and limits the antitumor immune response. These two unique functions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 155 publications
(237 reference statements)
0
25
0
Order By: Relevance
“…Short-term treatment of the macrophages with inhibitors of transcription or translation (actinomycin D or cycloheximide, respectively) prior to MSP stimulation completely abrogated MSP-mediated upregulation of CD80 and PD-L1 (Figure 2a). Since RON can signal through both MAPK and PI3K pathways to control gene expression, 26,31 we tested the activity of, and the requirement for, these two signaling nodes in the regulation of CD80 and PD-L1. Western blot analysis of MSP-treated macrophages revealed phosphorylated forms of ERK and AKT as surrogates of MAPK and PI3K pathway activation, respectively (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Short-term treatment of the macrophages with inhibitors of transcription or translation (actinomycin D or cycloheximide, respectively) prior to MSP stimulation completely abrogated MSP-mediated upregulation of CD80 and PD-L1 (Figure 2a). Since RON can signal through both MAPK and PI3K pathways to control gene expression, 26,31 we tested the activity of, and the requirement for, these two signaling nodes in the regulation of CD80 and PD-L1. Western blot analysis of MSP-treated macrophages revealed phosphorylated forms of ERK and AKT as surrogates of MAPK and PI3K pathway activation, respectively (Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…2528 Particularly, overexpression of RON in breast tumors is associated with increased metastasis and poor clinical outcomes. 16,26 In macrophages, activation of RON by MSP results in attenuation of immune responses. 2933 Previously, we and others have shown that host RON signaling negatively regulates antitumor immunity in mouse models of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…RON activation in cancer can occur through MSP-mediated stimulation of the receptor and/or by overexpression of the receptor independent of its ligand. 4 , 17 In order to examine both ligand-dependent and ligand-independent RON activation, we engineered human estrogen receptor positive breast cancer cells (T47D cells) to conditionally overexpress RON upon addition of doxycycline. This strategy enabled us to titer the expression level of RON by increasing the concentration of doxycycline.…”
Section: Resultsmentioning
confidence: 99%
“…Although they are less commonly expressed than full-length RON, alternative isoforms of RON have also been shown to mediate activation of different signaling pathways in several epithelial cancers. 17 An example of a constitutively active variant of RON is short-form RON (sfRON). We have previously shown that overexpression of sfRON in nonmetastatic MCF7 breast cancer cells was sufficient to convert them into fast-growing, metastatic tumors.…”
Section: Introductionmentioning
confidence: 99%
“… 10 11 12 13 14 15 16 17 At least nine types of RON isoforms have been identified: RONΔ170, RONΔ165, RONΔ165.e11p, RONΔ160, RONE5/6in, RONΔ155, RONΔp110, RONΔ85 and RONΔ55. 18 19 …”
Section: What Is Ron?mentioning
confidence: 99%